Variation of Processed Fresh Pineapple on Vitamin C Content Using UV-VIS Spectrophotometry - Mardiana Prasetyani Putri (Journal of Natural Sciences and Learning, 2023)
Important sources of vitamin C in food mainly come from fruits and vegetables. One type of fruit that contains vitamin C and is much in demand by the public is pineapple. To extend the shelf life of pineapple fruit can usually be done by processing the fruit into other preparations. But on the other hand the content of vitamin C in fruit and food will be damaged due to the oxidation process by the outside air, especially when heated. This study aims to determine the levels of vitamin C in fresh pineapple and processed varieties of pineapple. This research method is descriptive by analyzing the content of vitamin C in fresh pineapple and its processed variations using the UV-Vis spectrophotometry method. Based on the results of the study, the levels of vitamin C in fresh pineapple, pineapple syrup and candied pineapple were (95.75 ; 49.09 ; 44.09) mg/100g, respectively. Based on the statistical test results, a significant value of p>0.05 was obtained, which meant that the data was normal and continued with the paired parametric T test. The result of the test is p<0.05. There are differences in the value of vitamin C levels in fresh pineapple and processed variations.